PENGARUH PEMBERIAN EDUKASI GIZI TERHADAP PENGETAHUAN DAN SIKAP MENGENAI ANEMIA PADA REMAJA PUTRI - Rizqi Widyantori Hasanah Putra; j. Supadi; Wiwik Wijaningsih (JURNAL RISET GIZI, 2019)
Background  : The main nutritional problem that many teenagers experience is Anemia. The World Health Organization (WHO) predicts about 27% of female adolescents in developing countries suffer from anemia. anemia in adolescents can be caused by several things such as teenagers' knowledge and attitudes to anemia. The provision of nutritional education is expected to increase student knowledge and attitudes about nutrition in anemia, especially for female students.Objective  :  The aims to Knowing effect of Providing Nutrition Education on Knowledge and Attitudes Regarding Anemia in students SMP N 31 Semarang.Method  : This study uses the True Experiment method design with a mixture of pre test post test control group design. The sample consisted of 27 treatment groups and 27 control groups. The data collected were data on knowledge and attitudes regarding anemia nutrition. The data explorer uses a questionnaire that was filled in by the respondent himself. Data analysis using Man Whitney test, Independent T Test and Anova Repeater measure.Result  : There was an effect of providing nutrition education on female students 'knowledge of anemia (p = 0,000) and there was an influence on the provision of nutrition education on female students' attitudes about anemia (p = 0,000).Conclusion  : The provision of nutritional education affects the knowledge and attitudes about anemia in Semarang City 31 Junior High School Students.